Treating number transcoding difficulties in a chronic aphasic patient. - Ablinger I; Weniger D; Willmes K (Aphasiology, 2006)
Background: Number transcoding comprises the ability to read and write Arabic numerals and number words. Although number transcoding and counting are frequently impaired in aphasic patients, little attention has been given to the development of specific treatment methods and the evaluation of their efficiency. We report the treatment of the chronic aphasic patient PK who had severe difficulties in reading Arabic numerals. Number words could only be produced with an automatic counting strategy, always beginning with one.Aims: The therapy study was aimed at examining whether PK's numeral transcoding abilities could be improved by an intensive remediation programme that comprised tasks in which Arabic numerals had to be transcoded into number words.Methods & Procedures: Treatment consisted of specific training blocks of gradually increasing complexity. Therapy started with reading one-digit Arabic numerals, followed by teens, decades, and two- to five-digit numerals, which were divided into different subgroups according to complexity.Outcomes & Results: After an 8-week therapy period significant improvement in the processing of one- to five-digit numbers was observed. PK was able to read 49.4% of the Arabic numerals as compared to 2.2% before treatment. Performance was influenced significantly by number length and number word structure. Transcoding abilities improved remarkably for two- and three-digit numbers containing a zero or ending with two zeros. Stability of the treatment effects was assessed in a follow-up study 6 months after termination of the treatment programme. PK was still able to read 48.3% of the Arabic numerals successfully.Conclusions: In a single-case study of patient PK, suffering from chronic severe aphasia that was also characterised by severe transcoding and calculation impairments it could be demonstrated that these transcoding problems could be remedied to a substantial degree when employing a carefully graded intensive retraining programme for Arabic number naming.